Dignified Housing in Cuiabá-MT: An Analysis Based on IBGE’s 2022 PNADc Microdata - Rosso, Rafaela Ferreira; Souza, Natallia Sanches e; Ravache, Rosana Lia (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This research aims to analyze housing in Cuiabá using the 2022 PNADc microdata from IBGE, in order to understand how access to dignified housing has been provided in the capital. Methodology – A quantitative methodology was applied, based on secondary data, and tools such as R, RStudio, and Excel were used for data tabulation and analysis. Originality/Relevance – The research stands out for its originality, as there are no previous studies addressing the issue of housing conditions in Cuiabá from this perspective. Furthermore, it uses an innovative methodological approach by exploring PNADc data with a focus on household analysis. Results – The results indicated that many residences in Cuiabá do not meet essential adequacy criteria, such as those established by NBR 15220/03 and the João Pinheiro Foundation (FJP). Theoretical/Methodological Contributions – The research provides a significant theoretical and methodological contribution, as the theme of dignified housing in Cuiabá had not been explored in previous academic studies. Additionally, the database used is innovative, having only been employed in research of other natures up until now. Social and Environmental Contributions – This study offers important insights into the weaknesses related to dignified housing, and its findings may guide future initiatives and policies aimed at improving housing conditions in the municipality.